Transforming the Big Box Landscape: Walkable and Multi-functional Town Centres - Divakaran,Chaithanya (2025)
This thesis addresses the challenge of transforming car-oriented, mono-functional big-box landscapes into multi-functional, walkable local-centre. It assembles an integrated framework from recent research and translates it into a design approach to be tried in a case study. In contrast to the proposed multi-functional approach, a monocentric urban system concentrates functions and advantages in a single dominant core, leaving many residents with longer routine trips and uneven access. Studies stress that polycentricity performs best when centres are integrated and connected by efficient transit systems. Multi-functionality, coupled with the public realm, is a reliable route to everyday urban life, while inward-facing retail formats with parking erode permeability and street vitality. Hence, the thesis adopts a proximity-based accessibility lens, securing nearly equal access to different kinds of everyday opportunities and organising them so users can reach one activity within a 15-minute walk. It also positions walkability and urban greening as health and equity levers and studies pedestrian dynamics to guide design that reduces friction, simplifies decisions, and makes legible, direct routes that are supported by inclusive, child-friendly measures such as raised crossings, protection at conflict points, shading, tactile cues, good lighting, and passive surveillance. This thesis applies these strategies and principles in a real-world setting to learn from its application by • Reallocating street space to walking and cycling. • Connecting nodes via transit and clear bike or walk networks. • Planning for proximity and variety (10–15-minute reach). • Re-parcelling and re-fronting big-box plots. • Curating active ground floors with everyday services. • Adding civic anchors to stabilise footfall The case is in City Syd in Skalborg, Aalborg, a big-box landscape, positioned to benefit from a high-capacity public-transport spine. The design proposal tests how the above strategies can convert a car-led retail zone into a recognisable local centre within a polycentric network. In short, the project demonstrates how the Skalborg case study can transform big-box territories into vibrant local centers where daily life is accessible, pedestrian-friendly, and centers are defined by variety, connectivity, and care.
Keywords: Big-Box Landscape; Multifunctional; Polycentricity; Walkability